The study on the effectiveness of Corporate Social Responsibility (CSR) by Petronas in penetrating international markets / Wan Nurul Nadiah Wan Khairuldin - Wan Khairuldin, Wan Nurul Nadiah (2010)
This study is conducted as a partial fulfillment of the coursework of Project Paper (IBM 662). Title of the study is “The Study of the Effectiveness of Corporate Social Responsibility (CSR) by PETRONAS in penetrating International Markets”. The main objective of the study is to determine at what point PETRONAS has effectively promoting its CSR in expanding their investment for oil and gas in the countries with huge natural reserves. The CSR practices should not be mistaken as acts of charity or philanthropy. On the contrary, effective adoption of CSR has the twin effects of improving both short term and long term corporate performance. CSR efforts allow companies to distinguish themselves from competitors, and add value to their brand. Better brand value proposition translates to better client and customer satisfaction especially in a world where consumers, employees and investors are becoming more discerning. Brand reputations can be enhanced if the causes that such companies support and represent are ethically or socially laudable. The perception of the brand as socially responsible can often influence customer loyalty, lender and investor scrutiny, and ultimately reduce the cost of capital. From a national stand point, strong brands will also allow Malaysian companies to compete effectively in the global market. This study was conducted under two types of data collection; Primary Data and Secondary Data. The Primary Data was collected discussion with staffs at Corporate Social Department and also with staff’s of Accounts and Finance Department, while the Secondary Data was collected from various sources such as internet, magazines, journals, book and articles. This case study will highlight certain benefit of doing CSR which should be noted by all other companies that intended to invest in other countries for the future benefit rather than used other strategy of attack that countries as done by US to attack Iraq for one of the reason to get the oil and gas reserves.